Efficacy and safety of Viltepso® in Duchenne muscular dystrophy: review of clinical studies - V. M. Suslov; D. I. Rudenko (Русский журнал детской неврологии)
The author presents a literature review on the safety and efficacy of antisense oligonucleotides in the treatment of Duchenne muscular dystrophy using the exon skipping method using Viltepso® (viltolarsen), the only drug of this class registered in Russia, as an example. The analysis of international publications on clinical trials showed a high level of efficacy and safety of Viltepso®. This article, among other things, describes a 4-year clinical trial of viltolarsen. To date, this is the longest clinical trial of drugs of this group for the treatment of Duchenne muscular dystrophy. At the same time, it should not be forgotten that any pathogenetic therapy for Duchenne muscular dystrophy does not cure, but only slows down the progression of the disease, transferring it to a clinical form similar to Becker muscular dystrophy, provided that therapy is started early. In this regard, none of the currently available pathogenetic therapy can be considered as a monotherapy for the disease. Pathogenetic therapy will be most effective and will bring the desired results only with timely initiation of treatment and in combination with glucocorticosteroid therapy, symptomatic therapy and medical rehabilitation.